Design and numerical analysis of a gap-compensated low loss hollow-core antiresonant fiber with nested elliptical tubes - Yuemei Li; Zhaoyang Zhang; Yao Guo; Haobo Guo; Zhiguo Zhang (Scientific Reports)
Abstract In this research, we propose a novel hollow-core anti-resonant fiber structure designed to enhance light confinement and reduce losses. Our simulation results indicate that the LP01 mode loss is reduced to 1.807 × 10⁻⁶ dB/km at a wavelength of 1.52 μm, representing an extremely low confinement loss. Additionally, our model exhibits strong bending resistance, maintaining a bending loss of 4.81 × 10⁻⁵ dB/km at a wavelength of 1.55 μm and a bending radius of 6 cm. The dispersion is also maintained at 1 ± 0.7 ps/(nm·km), ensuring low dispersion characteristics. These features suggest its potential for applications in hollow-core fiber-based low-latency telecommunication systems.